Intramedullary Spinal Cord Tumors: Part II—Management Options and Outcomes. (March 2016) - Samartzis, Dino; Gillis, Christopher C.; Shih, Patrick; O'Toole, John E.; Fessler, Richard G.
Study Design: Broad narrative review. Objectives: Intramedullary spinal cord tumors (IMSCT) are uncommon lesions that can affect any age group or sex. However, numerous IMSCT exist and the clinical course of each tumor varies. The following article addresses the various management options and outcomes in patients with IMSCT. Methods: An extensive review of the peer-reviewed literature was performed, addressing management options and clinical outcomes of patients with IMSCT. Results: Early diagnosis and intervention are essential to obtain optimal functional outcome. Each IMSCT have specific imaging characteristics, which help in the clinical decision-making and prognostication. A comprehension of the tumor pathology and the clinical course associated with each tumor can allow for the proper surgical and nonsurgical management of these tumors, and reduce any associated morbidity and mortality. Recent advances in the operative management of such lesions have increased the success rate of tumor removal while minimizing iatrogenic-related trauma to the patient and, in tandem, improving patient outcomes. Conclusions: Awareness and understanding of IMSCT is imperative to design proper management and obtain optimal patient outcomes. Meticulous operative technique and the use of surgical adjuncts are essential to accomplish proper tumor removal, diminish the risk of recurrence, and preserve neurologic function. Operative management of IMSCT should be individualized and based on tumor type, location, and dimensional extensions. To assist with preoperative and intraoperative decision-making, a general algorithm is provided.